ANTIMICROBIAL PROPERTIES OF POLYMER FILMS WITH XEROFORM - KUCHYNSKA, DARIA; ISHCHENKO, OLENA; KACHAN, ROMAN; ROIK, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
To investigate the potential of novel wound-healing dressings, a comprehensive study was undertaken to evaluate the antimicrobial and antifungal efficacy of composite polymer films based on modified starch (MS) and polyvinyl alcohol (PVA), incorporating 10 wt.% xeroform. To rigorously assess the bioactivity of these developed films, the agar diffusion method was employed, utilizing a panel of clinically relevant microorganisms. This panel comprised the Gram-negative bacterium Escherichia coli, the Gram-positive bacterium Staphylococcus aureus, the yeast-like fungus Candida albicans, and the filamentous fungus Aspergillus niger, all recognized as common etiological agents of secondary wound infections. Discovered significant antibacterial and antifungal activity exhibited by the MS/PVA films incorporating xeroform. These results robustly confirm the substantial potential of these composite materials as bioactive wound dressings, capable of mitigating microbial colonization and infection. A particularly noteworthy aspect of this research is the inherent tunability of material properties through controlled modification of the starch component. This versatility offers promising avenues for tailoring film characteristics to meet diverse functional requirements in wound management and other biomedical applications. Future research endeavors will be strategically directed towards in-depth investigations of the biocompatibility profile of these novel materials. Furthermore, studies will be conducted to elucidate and optimize the drug release kinetics, specifically examining the sustained release capabilities of medicinal substances from the polymer matrix. These subsequent investigations will be critical to providing a comprehensive evaluation of the translational potential and ultimate clinical utility of these innovative composite films in medical practice.